The use of total physical response in teaching reading comprehension to Year Three Intan Pupils / Syarifah Sabira Syed Baharom - Syed Baharom, Syarifah Sabira (Faculty of Education, 2015)
The effect of using Total Physical Response (TPR) on student's understanding for learning English in classroom was investigated. Pre and post- test were used to record changes in the effectiveness for learning English during a four week study period. The purpose of this research is to investigate the use of TPR in teaching reading comprehension to Year Three Intan Pupils in SK Meru Jalan Tap. The method used in this study is based on the TPR activity conducted by the researcher to a group often students, in the classroom. The main reason is to aid pupils in Year Three Intan to be able to understand the text that they read and finally answer questions orally and in written works pertaining to the text that they read. In this study, the researcher investigated how the implementation of TPR into her ten weakest students from Three Intan would impact their understanding of answering comprehension text. Answering comprehension text can be defined as the students' ability to answer the question based on the linear text orally and in written work provided by the researcher. Her motivation for focusing on TPR was twofold. First, as a teacher, the researcher have had interest in using TPR into her lesson in order to make the class have more fun. Secondly, the method recently became useful with the new KSSR curriculum that need students to be more active in the classroom. In this study her students had an opportunity to actively engage with the lesson as they explored by involving physically in the activity conducted by the researcher.